Diagnostic significance of micronucleus evaluation in breast fine needle aspiration cytology - N., Binia Sherin; S., Sumathi (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is one of the most common malignancies among females in India. Micronucleus (MN) scoring, a marker of chromosomal instability, has shown potential in evaluating breast lesions cytologically. The International Human Micronucleus Project confirmed that MN assays are simple and minimally invasive indicators of genomic instability, with higher scores correlating with malignancy. To compare MN scores across benign, borderline and malignant breast lesions, correlate MN scores with Robinson’s cytological grading in malignant cases and evaluate the diagnostic utility of MN scoring in fine needle aspiration cytology (FNAC). Methods: A cross-sectional study was conducted in the Department of Pathology of Melmaruvathur Adhiparasakthi Institute of Medical Sciences and Research from December 2023 to February 2025 on 100 breast FNAC samples. Smears were alcohol-fixed, H&E-stained and classified per the Yokohama System. Robinson’s cytological grading was applied to malignant cases and MN scoring was performed on 1000 cells per case. Statistical analysis was done using SPSS version 20, with p<0.05 considered significant. Results: Among 100 cases (age 19–62 years), there were 50 benign, 10 atypical, 10 suspicious and 30 malignant lesions. Mean MN scores were 0.53±0.45, 2.8±0.85, 6.4±2.1 and 21.9±5.9, respectively (p=0.000). Significant differences were found between most groups, except benign versus atypical (p=0.15). MN scores increased with Robinson’s grades I–III, showing significant correlation (p=0.04). Conclusions: Micronucleus scoring, reflecting genomic instability, serves as a simple, cost-effective adjunct cytological marker enhancing diagnostic accuracy and prognostication in breast malignancy.